2011
DOI: 10.1111/j.1475-6765.2010.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Polls, coalition signals and strategic voting: An experimental investigation of perceptions and effects

Abstract: Polls and coalition signals can help strategic voters in multiparty systems with proportional representation and coalition governments to optimise their vote decision. Using a laboratory experiment embedded in two real election campaigns, this study focuses on voters' attention to and perception of polls and coalition signals. The manipulation of polls and coalition signals allows a causal test of their influence on strategic voting in a realistic environment. The findings suggest that active information acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 51 publications
0
63
1
2
Order By: Relevance
“…It has also received convincing support from experimental evidence (Forsythe et al 1993;Forsythe et al 1996) and from observational data (Cox 1997). An example is the Meffert and Gschwend (2007a) experiment, which documents the strong impact that party cues can have on coalition-directed voting. Bowler, Karp, and Donovan (2010) present evidence that New Zealand voters condition their vote on the electoral prospects, as reflected in public opinion polls, of different coalition formations.…”
Section: Coalition Partners (γ C J N ) Administrative Responsibilitymentioning
confidence: 99%
“…It has also received convincing support from experimental evidence (Forsythe et al 1993;Forsythe et al 1996) and from observational data (Cox 1997). An example is the Meffert and Gschwend (2007a) experiment, which documents the strong impact that party cues can have on coalition-directed voting. Bowler, Karp, and Donovan (2010) present evidence that New Zealand voters condition their vote on the electoral prospects, as reflected in public opinion polls, of different coalition formations.…”
Section: Coalition Partners (γ C J N ) Administrative Responsibilitymentioning
confidence: 99%
“…We follow formulas (3) and (4) because of their simplicity and straightforwardness (cf. [24]). This way is the easiest possibility to estimate policy outputs depending on the coalition C and the sizes of C's members.…”
Section: The Modelmentioning
confidence: 99%
“…An experimental survey study from the mixed German system (Huber & Faas ) found that the established liberal party FDP gains votes from relatively low poll levels, whereas the less established parties receive higher shares when their poll levels increase towards the threshold. In another survey experiment conducted in Austria and Germany, Meffert and Gschwend () found that strategic voting for smaller parties occurred in the cases in which the representation of the smaller party was at stake. The impact of coalition signals is only briefly discussed in this study.…”
Section: Context Impactmentioning
confidence: 99%
“…Most previous studies of the relationship among coalitions, polls and strategic voting use various types of experimental survey research designs (Meffert & Gschwend 2011;Irwin & Holsteyn 2012;Huber & Faas 2014). However, in the study from the Dutch system (Irwin & Holsteyn 2012), the same participant is exposed to a number of different treatments, which may lead to spillover effects from one treatment to the other, ultimately affecting the overall results (see Transue et al 2009).…”
Section: A Survey Experimentsmentioning
confidence: 99%
See 1 more Smart Citation